INQUIRY ABOUT THE EFFECTS OF THE HYPONATREMIA IN PARTICIPANTS OF HALF MARATHON OF RIO DE JANEIRO EDITION 2007. (Fiep Bulletin - online, 2014)
The hiponatremia is a water-electrolyte imbalance. OBJECTIVE - To investigate, if the athletes who had participated in the half marathon of Rio de Janeiro 2007 edition and that needed medical cares, had presented some symptom that can be related to the hyponatremia. SUBJECTS - 20 subjects with age between 18 and 39 years that had participated of the half marathon of Rio de Janeiro 2007, of these 12 were men and 8 women. The choice of these subjects was made in the following manner: the first 20 participants of the event that needed medical care could be part of the free study in spontaneous will. METHODOLOGY - Research with exploratory bias and quantitative characteristics. The choice of an appropriate method was based on the relative precision, the trustworthiness and the exactness of the available methods and on the existence of available resources that that go in the direction of the interests considered for the study in function of the reality. RESULTS - the symptoms observed had been: disorientation, confusion, agitation, slurred speech, respiratory difficulties, cramps, nausea, convulsion and lethargy. We observe that 50% of the athletes who had needed medical cares had presented 3 related symptoms with the hyponatremia and that only 5 % with symptoms. DISCUSSION - It was observed that diverse symptoms of hyponatremia had been common during the half marathon of Rio de Janeiro in 2007. However we cannot affirm that all the symptoms were indicative of hyponatremia, because some symptoms of the dehydration are similar with the hyponatremia symptoms, such as cramps and muscular weakness. CONCLUSION - We must give more attention to hyponatremia, starting to investigate it more seriously in national events. The type of analysis used in our study cannot be considered the most insured, hence being an invasive observational study. For better analysis of hyponatremia an evaluation of serum sodium would be necessary.
Keywords: Hyponatremia; dehydration; water-electrolyte imbalance